Tungguroni Community Service Through Stunting Counseling Activities and Socialization of Healthy Eating Patterns with the Dashat Menu - Nasution, Fadya Safira; Hafizah, Casyariadi Vana; Mandalika, Mandalika; Syahputri, Siti Novi Astri; Mayasari, Ulfayani (Jurnal Abdi Mas Adzkia, 2023)
Abstract Stunting is a condition of failure to thrive in children due to chronic malnutrition that occurs in the first 1,000 days of life, starting from pregnancy until the child is 2 years old. In order to overcome the problem of stunting, outreach activities are one of the effective methods. This outreach will provide the public with an understanding of the importance of balanced nutrition and adequate nutritional intake for the growth and development of children. Objective from study This For increase awareness public about danger of stunting and method handle it so that it can be done lower risk of stunting in child . The implementation method used by researchers in this KKN activity consists of several activities, including implementing Stunting Socialization and Counseling as well as Providing Dashat Menus to the Community in nggurono Subdistrict which is the Center for Providing Health Education related to Stunting. The implementation of outreach activities was also supported by the Binjai City Genre Party, they sent Stunting Care Genre Ambassadors to contribute to this activity. And the presence of several Family Planning Field Officers (PLKB) also enhances stunting education activities. Socialization of Healthy Eating Patterns with the DASHAT Menu is carried out by KKN Students, by demonstrating healthy cooking for pregnant women and breastfeeding mothers, as well as introducing food ingredients that can be consumed and food ingredients that should be avoided during pregnancy and breastfeeding, as well as demonstrating cooking for toddlers and toddlers.